The Application of the Typeface in the Signage System - Zhang, Yinghui (Journal of Theory and Practice of Social Science, 2024)
Due to the expansion of the highway system and the continuous growth of traffic, the safety issues associated with the dissemination of traffic information have become more important. This study reviews the literature on the legibility of typeface used in highway signage systems and the types of fonts used in highway systems, focusing on the most significant findings on the characteristics of typefaces and the features that most affect legibility. The findings of this research identified the humanity typeface can help to satisfy the need for people to navigate from one place to another, then to create a clear and concise wayfinding system.